Project to include Index Sheets in the Polish National Bibliography of Cartographic Materials - Szaniawskã, Lucyna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
The first post-war volume of the Bibliographical Guide was published in 1946. As an official index of monographic publications it gives a description of all the publications based on legal deposits received by the National Library of Poland [Biblioteka Narodowa]. Bibliographic descriptions are standardized in accordance with Standard PN-82/N-01152.01 Bibliographic Book Description, which has been in force in Poland since 1984 (Sadowska, 2001). The descriptions must also comply with the requirements of the 1986 publication Book Cataloging Rules (Lenartowicz, 1986). The rules laid down in both above‑mentioned documents comply with the international regulations formulated by the International Federation of Library Associations (IFLA) and are commonly known as ISBD(M) which, for the purpose of creating descriptions for the Bibliographical Guide came into use as early as 1976.